Ecosystem‐based fisheries management in the Northwest Atlantic - Jason S Link; Alida Bundy; William J Overholtz; Nancy Shackell; John Manderson; Daniel Duplisea; Jon Hare; Mariano Koen‐Alonso; Kevin D Friedland (Fish and Fisheries, 2011)
The northwest Atlantic has had a notable history of living marine resource (LMR) exploitation. There have been calls for evaluating and improving approaches to manage those resources as stocks have undergone sequential depletion, with some dramatic instances of stock declines. The need for more holistic ecosystem‐based approaches to manage LMRs has been increasingly recognized as part of these calls, along with the recognition that there are broader issues to consider when managing a fishery. We discuss some of the major efforts to this end which are extant among our institutions. We emphasize current initiatives to implement ecosystem‐based fisheries management in the northwest Atlantic, with a focus on how advice based on the natural sciences supports an ecosystem‐based approach. We present this information as a case study within a rich historical context of fisheries science and management.